Characterization of a Novel Orbivirus from Cattle Reveals Active Circulation of a Previously Unknown and Pathogenic Orbivirus in Ruminants in Kenya - Dorcus C. A. Omoga; David P. Tchouassi; Marietjie Venter; Edwin O. Ogola; Solomon Langat; Caroline Getugi; Georg Eibner; Anne Kopp; Inga Slothouwer; Baldwyn Torto; Sandra Junglen; Rosemary Sang (mSphere, 2023)
ABSTRACT Arboviruses are among emerging pathogens of public and veterinary health significance. However, in most of sub-Saharan Africa, their role in the aetiologies of diseases in farm animals is poorly described due to paucity of active surveillance and appropriate diagnosis. Here, we report the discovery of a previously unknown orbivirus in cattle collected in the Kenyan Rift Valley in 2020 and 2021. We isolated the virus in cell culture from the serum of a clinically sick cow aged 2 to 3 years, presenting signs of lethargy. High-throughput sequencing revealed an orbivirus genome architecture with 10 double-stranded RNA segments and a total size of 18,731 bp. The VP1 (Pol) and VP3 (T2) nucleotide sequences of the detected virus, tentatively named Kaptombes virus (KPTV), shared maximum similarities of 77.5% and 80.7% to the mosquito-borne Sathuvachari virus (SVIV) found in some Asian countries, respectively. Screening of 2,039 sera from cattle, goats, and sheep by specific RT-PCR identified KPTV in three additional samples originating from different herds collected in 2020 and 2021. Neutralizing antibodies against KPTV were found in 6% of sera from ruminants (12/200) collected in the region. In vivo experiments with new-born and adult mice induced body tremors, hind limb paralysis, weakness, lethargy, and mortality. Taken together, the data suggest the detection of a potentially disease-causing orbivirus in cattle in Kenya. Its impact on livestock, as well as its potential economic damage, needs to be addressed in future studies using targeted surveillance and diagnostics. IMPORTANCE The genus Orbivirus contains several viruses that cause large outbreaks in wild and domestic animals. However, there is little knowledge on the contribution of orbiviruses to diseases in livestock in Africa. Here, we report the identification of a novel presumably disease-causing orbivirus in cattle, Kenya. The virus, designated Kaptombes virus (KPTV), was initially isolated from a clinically sick cow aged 2 to 3 years, presenting signs of lethargy. The virus was subsequently detected in three additional cows sampled in neighboring locations in the subsequent year. Neutralizing antibodies against KPTV were found in 10% of cattle sera. Infection of new-born and adult mice with KPTV caused severe symptoms and lead to death. Together, these findings indicate the presence of a previously unknown orbivirus in ruminants in Kenya. These data are of relevance as cattle represents an important livestock species in farming industry and often is the main source of livelihoods in rural areas of Africa.